NILAI-NILAI DASAR AQIDAH AKHLAK DIMENSI RABBANI, PERSONAL, SOSIAL, DAN GLOBAL - Sifa Fauziah; Muhammad Aulia Afdal; Eka Putra Wirman; Hasnah; Rahmat (As-Sulthan Journal of Education, 2026)
Aqidah and akhlaq are two main pillars in the formation of a complete, balanced Muslim personality in accordance with Islamic teachings. Aqidah serves as the foundation of belief, while akhlaq represents the manifestation of that belief, forming an inseparable unity. This article aims to examine the fundamental values of aqidah akhlaq across four dimensions: rabbani (divine), personal, social, and global. This study employs a qualitative library research method, with primary data sources consisting of the Qur’an, the hadiths of the Prophet Muhammad (peace be upon him), and the book Minhājul Muslim, as well as secondary data derived from tafsir (Qur’anic exegesis), hadith commentaries, and related academic literature. The data are analyzed using a descriptive-interpretative approach to interpret and classify the values of aqidah akhlaq into the four dimensions. The findings indicate that understanding and implementing rabbani, personal, social, and global values are essential in shaping Muslim character that is faithful, morally upright, and socially as well as globally responsible. This study provides a conceptual contribution to the development of aqidah akhlaq education in both individual and societal contexts.